Pengembangan E-Book Interaktif Berbasis Canva pada Materi Komunikasi Lisan Bahasa Indonesia Kelas XI MPLB SMKN 62 Jakarta - Indah Susanty; Roni Faslah; Mayang Riyantie (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
Vocational education in Vocational High Schools (SMK) requires innovative, interactive, and industry-relevant learning media to support students’ independent and competency-based learning. However, learning activities in the subject Communication in the Workplace for Grade XI MPLB at SMKN 62 Jakarta are still dominated by lecture-based methods with limited instructional media, resulting in low levels of student independence and understanding. This study aimed to develop and examine the feasibility, practicality, and effectiveness of an interactive e-book based on Canva for Oral Communication materials in Indonesian Language. The study employed a Research and Development (R&D) method using the ADDIE development model, consisting of analysis, design, development, implementation, and evaluation stages. The research subjects included 36 students in the needs analysis stage, 5 students in the small-scale trial, and 31 students in the large-scale trial. Data were collected through observation, questionnaires, learning outcome tests, and documentation, and analyzed using descriptive qualitative and quantitative techniques. The validation results indicated that the Canva-based interactive e-book was categorized as very feasible, with validation percentages of 100% from the material expert, 88.24% from the media expert, and 95% from the language expert. The small-scale trial showed a practicality percentage of 82.2%, while the large-scale trial reached 88.39%, both classified as very practical. In addition, the pre-test and post-test results in the large-scale trial demonstrated an increase in students’ average scores and a higher number of students achieving the Minimum Mastery Criteria (KKM). Therefore, the Canva-based interactive e-book is feasible, practical, and effective as a learning medium to enhance students’ understanding, motivation, and independent learning in Oral Communication for vocational high school students.